PVC Plant Design - Estrada, Ramon; Lim, Victorio; Reyes, Juan; Vizcarra, Rosario J. (College of Engineering, 1966)
This plant is designed to produce 20 tons of pure PVC per day using acetylene-hydrogen chloride process for the synthesis of vinyl chloride and emulsion method for the polymerization of the VC to PVC. In the synthesis, a tubular reactor is used since the reactants are both gases. The production of the monamer is with the aid of a catalyst - impregnated charcoal, i.e., Hg2Cl2 on activated carbon. The emulsion method of polymerization is chosen because of the high conversion it is capable of and from literature, 90% conversion in 24 hours is obtainable. This method requires a batch reactor. The product obtained using emulsifiers contains the soap as impurities. The proposed plant, thus, produces 95.8% pure PVC and with a total output of 20.91 tons per day. With this output of 20.91 tons per day, an investment of approximately 29 million pesos is required and the plant needs 25 million pesos for its operation per annum. The total sales from the product PVC is 6 million pesos and this income is increased to ll million pesos as the by-products - slaked lime, stripped acid and the condensed acid (21% HCl, 37.2% HCl, & 42.25% HCl) - are sold. Therefore, this plant loses 14 million pesos annually if operated and as such, it is not economically feasible.